Sustainability in Air Transport and Multimodality - Di Vito, Vittorio; Duca, Gabriella; Russo, Raffaella (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint addresses fundamental research about the integration of transport modes into unique mobility infrastructure and services, allowing for multimodal choices for passengers in their journey and increasing the sustainability of mobility. The reprint has important relevancy given the increasing attention devoted to sustainability aspects in aviation and the emerging need to achieve multimodality in transportation, by integrating the vertical dimension with the horizontal one, particularly in urban and peri-urban environments. New technologies and concepts are considered for implementing seamless door-to-door travel, which requires the implementation of fully integrated intermodal transport systems, allowing for passengers to have easy and seamless transfer between different transport modes, where Air Traffic Management (ATM) and air transport can play a fundamental role. The new paradigm in transport is of shifting from the optimization of the individual transport segments to the optimization of the overall journey, including all the possible transportation means that allow for achieving, in combination and with multimodal possible choice, a unique seamless door-to-door journey. Through this new paradigm, it will be possible to increase the efficiency of the overall transport chain by improving the interoperability of the different modes of transport, while simultaneously increasing environmental, social, and economic sustainability, prompting a more efficient use of existing and future infrastructure.